Disinfection - Kırmusaoğlu, Sahra (IntechOpen, 2018)
Disinfection is a method used to destroy most microbial forms, especially vegetative pathogens, by using physical and chemical procedures such as chlorination, UV radiation, boiling, vapor, etc. Biotic surfaces such as skin and abiotic surfaces such as contaminated medical devices and kitchen equipment exposed to cross contamination must be disinfected. Especially, inadequate disinfection of water can be fatal and cause life-threatening outbreaks. For this reason, water must be disinfected adequately by appropriate methods. There are several factors that affect the efficacy of disinfection against pathogens, such as capacity of biofilm and spore formation, having antibiotic resistance, etc. It is hard to destroy bacterial biofilms, bacterial spores, and resistant microorganisms. Some bacterial spores and resistant microorganisms can withstand disinfectants, so adequate disinfection must be done by appropriate methods. The aim of this book is to summarize disinfection, disinfection methods, and chemical analysis of by-products by providing up-to-date topics.